Analisis Perubahan Tata Guna Lahan Terhadap Debit Limpasan Pada Subdas Air Betung - Elza Dewi; Alharia Dinata (JURNAL ILMIAH BERING'S, 2018)
The need for land is increasing as the population increases. To fulfill the settlement land and other needs, various efforts are carried out including the transfer of land functions. Improper land conversion will cause a run-off increase in a watershed. The runoff will experience peak discharge at any time and will cause flooding if the volume cannot be accommodated by drenase. This study aims to compare changes in land use to predict the peak flood discharge in the Air Betung sub-watershed in the 10-year re-preode. The research method uses DEM map analysis to obtain the area of ​​the watershed and the length of the main river. For rainfall distribution using two frequency analyzes in 2004-2013 and 2008-2017 and the chosen method is normal distribution. The peak discharge was calculated by the nakayasu synthetic unit hydrograph. Changes in peak discharge caused by land use changes in 2013 and 2017 experienced a change, where for 2013 the Cverages value was 0.36 and peak discharge was 151.37 m3 / sec and for 2017 the Cverages value was 0.33 and peak discharge was 138.95 m3/ sec.